Public Space Design Strategy Based on User Perception Through a Placemaking Approach (Case Study: Jogokariyan Cultural Religious Village, Yogyakarta) - Yogma Noor Dinara Gimnastiar; Geraldo Yoshua Nababan (International Journal Labs, 2025)
Public spaces are an important element in the social dynamics of society and the formation of urban aesthetics, impacting the surrounding environment. In recent years, the development of urban public spaces globally has been influenced by the concept of placemaking. In Jogokariyan Village, with the Jogokariyan Mosque as the center, many changes have occurred as adaptations to the rapid and massive development of the area as a religious and cultural site. These changes are not only visual but also functional. These pressures and changes present challenges, such as the potential loss of the unique characteristics of Jogokariyan Village. This research aims to formulate a strategy for the arrangement of public spaces in Jogokariyan Village based on the level and conditions of placemaking. The research method used is mixed methods, combining qualitative and quantitative approaches. The results showed that the Jogokariyan Mosque, the streets and pedestrian paths, as well as the fields and courtyards, had a very high level of placemaking, but some variables still require improvement. The Jogokariyan Mosque needs enhancement in the variables of safe, convenient, neighborly, and accessible; street spaces and pedestrian paths in the variables of active, fun, safe, and convenient; and fields and yards in the variables of safe, active, fun, special, neighborly, and convenient. The strategy for arranging public spaces in Jogokariyan Village is expected to strengthen the village’s distinctive characteristics, promote sustainability, and meet the needs and perceptions of its users.